A longitudinal and multicentre study of burnout and error in Irish junior doctors. Issue 1105 (9th June 2017) - O'Connor, Paul; Lydon, Sinéad; O'Dea, Angela; Hehir, Layla; Offiah, Gozie; Vellinga, Akke; Byrne, Dara
ABSTRACT: Background: Junior doctors have been found to suffer from high levels of burnout. Aims: To measure burnout in a population of junior doctors in Ireland and identify if: levels of burnout are similar to US medical residents; there is a change in the pattern of burnout during the first year of postgraduate clinical practice; and burnout is associated with self-reported error. Methods: The Maslach Burnout Inventory—Human Services Survey was distributed to Irish junior doctors from five training networks in the last quarter of 2015 when they were approximately 4 months into their first year of clinical practice (time 1), and again 6 months later (time 2). The survey assessed burnout and whether they had made a medical error that had 'played on (their) mind'. Results: A total of 172 respondents out of 601 (28.6%) completed the questionnaire on both occasions. Irish junior doctors at time 2 were more burned out than a sample of US medical residents (72.6% and 60.3% burned out, respectively; p=0.001). There was a significant increase in emotional exhaustion from time 1 to time 2 (p=0.007). The association between burnout and error was significant at time 2 only (p=0.03). At time 2, of those respondents who were burned out, 81/122 (66.4%) reported making an error. A total of 22/46 (47.8%) of the junior doctors who were not burned out at time 2 reported an error. Conclusion: Current levels of burnout are unsustainable and place the health of both junior doctors and their patients at risk.